The study of money demand and inflation in Malaysia/ Shahrulnizam Kamalzaman - Kamalzaman, Shahrulnizam (2000)
This study discussed the money demand in Malaysia and the inflation rate. This study aims to identify whether the interest rate affect the money demand of M1, M2 AND M3. On the other hand, this study also tries to prove whether inflation affects the money demand of M1, M2 and M3.